Frequency and associated factors for carbapenem-non-susceptible Bacteroides fragilis group bacteria colonization in hospitalized patients: Case control study in a university hospital in Turkey - ÖZAYDIN, AYŞE NİLÜFER; ALTINKANAT GELMEZ, GÜLŞEN; BİLGİN, HÜSEYİN; ÜLGER, NURVER; KORTEN, VOLKAN (ELSEVIER, 2021)
Purpuse: The carbapenem-resistant Bacteroides fragilis group (CR-BFG) bacteria have been reported in several countries recently with increasing global attention. The high incidence of CR-BFG isolated from our hospitalized patients has become an important problem. Therefore, we aimed to determine the frequency and associated factors for intestinal colonization by carbapenem-non-susceptible BFG (CNS-BFG) among adult patients hospitalized at intensive care units, neurosurgery and internal medicine wards in our hospital. Methods: Rectal swabs (n = 1200), collected from 766 patients between February 2014 and March 2015, were inoculated onto kanamycin-vancomycin-leaked blood agar containing 0.125 mg/L meropenem. The isolates were identified by MALDI-TOF MS. Susceptibility testing was performed by agar dilution method. The carbapenemase gene (cfiA) was detected by PCR. Logistic regression analysis was used to evaluate the associated factors for intestinal colonization by CNS-BFG. Results: A total 180 non-duplicate BFG isolates were obtained from 164 patients. Ten different species, including Parabacteroides distasonis (n = 46, 25.6%), and Bacteroides fragilis (n = 30; 16.6%), were identified. Twenty- five percent of the isolates were non-susceptible to meropenem (MIC >2 mg/L). The highest prevalence of meropenem resistant strains (MIC >8 mg/L) was detected among B. fragilis (n = 12), followed by Parabacteroides spp. (n = 4). All but one B. fragilis strains were cfiA gene positive. Hospital admission, increasing Charlson score, use of antibiotics; including carbapenems in past three months, colonization with other accompanying carbapenem-resistant Gram negative bacteria (Enterobacteriaceae, Acinetobacter baumannii and Pseudomonas aeruginosa), and having undergone surgical operations were significantly associated with RCS- BFG colonization. Conclusions: The high carriage rate of CNS-BFG in hospitalized patients may lead to worse clinical outcomes, such as serious infections and mortality, and deserves attention.
Keywords: Bacteroides fragilis group; Carbapenem resistance; Metallo-beta-lactamase. cfiA gene; Risk factors; ANTIMICROBIAL RESISTANCE; EMERGENCE; STRAINS